Microstrip Patch Antenna With A Complementary Unit Of Rhombic Split Ring Resonator (R-SRR) Structure - Abd. Aziz, Mohamad Zoinol Abidin; Hassan, Nornikman; Ahmad, Badrul Hisham; Zakaria, Zahriladha; Othman, Mohd Azlishah; Othman, Abdul Rani; Jano, Zanariah; Jusoff, Kamaruzaman (IDOSI Publications, 2013)

(untitled)
Hitherto,split ring resonator is becoming a popular structure in antenna design.The objective of this paper is to determine the effect of the rhombic complimentary split ring resonator structure (R-SRR) on microstrip patch antenna design.The basic microstrip patch antenna design is simulated in CST Microwave Studio simulation software.The findings show that the resonant frequency of this antenna is 2.40 GHz for Wireless Local Area Network (WLAN) application.The R-SRR structure has increased the gain and efficiency of microstrip patch antenna. Therefore,the users will get a better coverage of WLAN signal.The different number of split rings may offer attractive results in the future.